Identifikasi Komposisi Kimia dan Uji Aktivitas Antioksidan dari Biji Kurma (Phoenix dactylifera) - Yusraini Dian Inayati Siregar; Tarso Rudiana; Windi Riyadi (Syarif Hidayatullah State Islamic University, 2018)
Dates are a component of dates that have 6.10-11.47% of all dates. In some countries, dates are a major problem in the processing industry because the seeds currently only become waste. This research was conducted to determine the solvent that produces the largest yield using the soxhletation method and determine its antioxidant activity. Dates are disoxletasion with a variety of solvents n-hexane, diethyl ether, and ethanol. Also carried out the variation of extraction time for 1.5; 2; and 2.5 hours. Based on the results of the study showed that the results of the largest date seed extract were obtained using ethanol of 4.93% for 2.5 hours. Antioxidant activity of date palm seed extract (IC50) using DPPH ethanol extract method has IC50 of 2.27 ppm; n-hexane extract 8396.56 ppm; and diethyl ether extract 9826.88 ppm. Inhibition of date palm seed extract using the TBA method derived from ethanol extract of 98.22% at a concentration of 250 ppm. The results of the analysis using LC-MS showed that ethanol extract was thought to contain 13-hydroxyabscisic acid compound, 1-ethylidene-4-methylidene-2oxo-7-(propan-2-il)-tocahydro-1H-indent-5-il- 3-methylpent-2-enoate, 12-hydroxy-acid (8,10,14) -eicosatrienoic and 1-hydroxy-3- (pentadecanoiloxy) propan-2-il (5,8,11,14) -icosa-5, 8,11,14-tetraenoate. The results of the analysis using GC-MS on n-hexane extract showed 2,4-di-tert-butylphenol and 9-octadecenoic acid. Diethyl ether extract contains 9-octadecenoic acid and mono (2-ethylhexyl) benzocarboxylic acid.